An analysis of Japanese conversation in interview context - Shariff, Muhammad Haikal; Mamat, Roslina; Abdul Halim, Hazlina (Universiti Putra Malaysia Press, 2016)
Aizuchi or short utterance, and responses are some of the Japanese linguistic features. Each of them holds significant meaning and functions from the listener to the speaker. Therefore, this paper aims to analyze the occurrence of Aizuchi, short utterance, and responses in the interview context by Japanese native speakers. By using 15 episodes of Easy Japanese videos, the study found a few types of Aizuchi, short utterance, and responses produced by the interviewee in the interview conversation. From the data, it was found that Aizuchi (hai), short utterances (hai), and responses (hai) occurred the most in interviewees’ utterances. Each hai held significant functions to maintain the naturalness of Japanese conversations. It also indicates that the term hai are frequently used in the Japanese conversation regardless of the context. The findings showed that Aizuchi, short responses and responses occur in the Japanese conversation in the interview context. In addition, the use of the term hai also extensively occurred in the conversation either as the Aizuchi, short response or response.